Stated preferences for human Papillomavirus vaccination for adolescents in selected communities in Ibadan, Southwest Nigeria: A discrete choice experiment (2022)
Administration of the human papillomavirus (HPV) vaccine in early adolescence is effective in preventing cervical cancer, a common cancer in sub-Saharan Africa. Nigeria is in the pre-introduction era of the HPV vaccine. Understanding the preferences of the population for the vaccine can help design the HPV immunization program to ensure high uptake of the vaccine. This study explored the preferences for the HPV vaccine among stakeholders in selected communities in Ibadan, Nigeria. A discrete choice experiment survey based on six attributes of the HPV vaccine (which were the number of doses, the efficacy of the vaccine, cost of the vaccine, location of the service point, other benefits of the vaccine apart from prevention of cervical cancer and the odds of a side effect from the vaccine) was carried out in five communities. Data were analyzed using conditional and mixed logit models. Seven hundred community members were recruited, 144 (20.7%) were adolescents and 248 (35.4%) were males. In line with expectations, respondents preferred vaccines with higher efficacy, less severe side effects and lower costs. Preference heterogeneity was identified for adolescents that were less price-sensitive and other community members who were less likely to prefer using schools as the service point. The high socio-economic class preferred a vaccine that also prevents genital warts. There were variabilities in the preferences for the attributes of the HPV vaccine in the study communities. These variabilities need to be considered in the introduction of the HPV vaccine to ensure high uptake of the vaccine.